Depressive symptoms, visual impairment, and its influence on physical disability and functional limitation - Hairi, N.N.; Bulgiba, A.; Cumming, R.G.; Naganathan, V.; Mudla, I. (2011)
To the Editor: Depression and visual impairment occurs commonly in older people. Depression1,2 and visual impairment3,4 have been associated with poor physical function. There is evidence that treatment of depression improves physical function.5 Visual impairment is modifiable to a certain degree, because it may be corrected through surgery and use of optical devices. Studies have also shown that these two conditions coexist.6 It was hypothesized that older people with depression and visual impairment would have a higher prevalence of poor physical function than those with depression or visual impairment alone. The aim of this study was to determine the relationship between the combined effect of depressive symptoms and visual impairment on physical disability and functional limitation.